The mythic Indian - Boucher, James (Professor of French), author.
1 online resource.
Keywords: "The Mythic Indian: The Native in French and Québécois Cultural Imaginaries charts a genealogy of French and Québécois visions of the Amerindian. Tracing an evolution of paradigms from the sixteenth century to present, it examines how the myths of the Noble, Ignoble, and Ecological Savage as well as the Vanishing Indian and Going Native inform a variety of discourses and ways of thinking about Québécois culture. By analyzing mythic depictions of the Native Figure that originate at first contacts, this book demonstrates that an inextricable link exists between discourses as disparate as literature and science. This book will be of interest to scholars in French Studies, Francophone Studies, Indigenous Studies, Hemispheric Studies, Social Sciences, and Literary Studies"--